PERAN GURU TERHADAP PENGELOLAAN PEMBELAJARAN PADA PESERTA DIDIK DI SEKOLAH INKLUSIF - Fitria Ningsih, Endang; Khofidotur Rofiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand the role of teachers in managing learning for students in inclusive schools with a focus on strategies and practices that support the needs of students with diversity. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with teachers and analysis of school documents. The results of the study indicate that teachers play a crucial role in creating an inclusive and adaptive learning environment, as well as supporting the special needs of students. Teachers also play a role in developing individual learning plans and using diverse learning methods to meet students' needs. This study concludes that the role of teachers is crucial in managing learning for students in inclusive schools, and teachers need to have appropriate skills and knowledge to manage learning in inclusive schools. To develop skills in learning management, researchers convey the importance of training and support for teachers to improve their abilities in managing learning in inclusive schools. These findings contribute to the understanding of the role of teachers in improving the quality of inclusive education and provide recommendations for the development of more inclusive education policies and practices.